The reliability and validity of two different inertial measurement units in youth basketball players - Palmer, B. L.; Van der Ploeg, G. E.; Bourdan, P. C.; Crowther, R. G. (Journal of Physical Education and Sport, 2023)
Approach: Technology, such as the inertial measurement unit (IMU), is frequently used in elite sporting environments for monitoring athlete stress and assessing performance. IMUs have been found to be reliable during test-retest in research conducted using adult participants however, there is a lack of information regarding the use of IMU devices with youth athlete sporting teams. Purpose: Therefore, this study aimed to evaluate the test-retest reliability and validity of two different IMUs (VX Sport and Blue Trident) for player load analysis in youth athletes. Additionally, a secondary aim was to compare the difference in player load analysis using an IMU (Blue Trident) at two difference locations (2nd thoracic vertebrae and lateral malleolus). Methods: Ten state-level youth basketball players participated in this study. Participants performed a multi-directional movement circuit while wearing two IMUs at the 2nd thoracic vertebrae (VX Sport and Blue Trident), and an additional IMU (Blue Trident) at the lateral malleolus on three separate testing sessions. Results: Moderate to good reliability was demonstrated for the VX Sport IMU and Blue Trident IMU (ICC = 0.64 to 0.86). There was no difference between sessions for each IMU. The VX Sport IMU at the 2nd thoracic vertebrae resulted in a reduced player load outcome compared to the Blue Trident IMU. Additionally, the Blue Trident IMU at the lateral malleolus had an increased player load outcome compared to the Blue Trident IMU at the 2nd thoracic vertebrae. Conclusion: All IMUs used in this study were reliable for testing youth athletes. Practitioners should not compare results between different technological devices without considering the potential sources of error, especially when undertaking cross and longitudinal analyses. Furthermore, where the IMU is placed will provide different analysis of accumulated load.